2012
DOI: 10.1007/s10517-012-1641-8
|View full text |Cite
|
Sign up to set email alerts
|

Study of Hypoglycemic Activity of Subetta and Rosiglitazone on the Model of Streptozotocin-Induced Diabetes Mellitus in Rats

Abstract: Antidiabetic activity of Subetta was revealed on the model of streptozotocin-induced diabetes mellitus in rats. Intragastric administration of this preparation in a dose of 5 ml/kg for 50 days reduced blood glucose levels, urine levels of glucose and ketone bodies, restored glucose tolerance in the oral glucose test, improved general condition and increased the survival rate of animals. The effectiveness of the drug was not inferior to that of rosiglitazone (8 mg/kg).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 4 publications
1
19
0
1
Order By: Relevance
“…Previously, Subetta demonstrated the ability to reduce hyperglycemia and improve glucose tolerance in various experimental models of diabetes mellitus and its effects were similar to that of rosiglitazone [14, 15]. Subetta was given by oral gavage, when it was studied in vivo but in the current study the direct action of Subetta on mature human adipocytes was estimated in vitro .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Previously, Subetta demonstrated the ability to reduce hyperglycemia and improve glucose tolerance in various experimental models of diabetes mellitus and its effects were similar to that of rosiglitazone [14, 15]. Subetta was given by oral gavage, when it was studied in vivo but in the current study the direct action of Subetta on mature human adipocytes was estimated in vitro .…”
Section: Resultsmentioning
confidence: 92%
“…In two DM animal models, streptozotocin-induced DM [14] and spontaneous T2D in Goto Kakizaki rats [15], Subetta showed antidiabetic effects similar to that of rosiglitazone. Additionally, Subetta has shown promising results in its first clinical use in both type 1 diabetes (T1D) patients with poor glycemic control receiving intensive insulinotherapy and T2D patients receiving metformin/combination of basal insulin with metformin (unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…The third group (PGK3 group) was given Subetta (5 mL/kg body weight) once a day, as a water solution (2.5 mL/kg body weight of RAD of Abs to β -InsR + 2.5 mL/kg body weight of RAD of Abs to eNOS). The dose of Subetta was the same as that used in the previous study in rats with streptozotocin-induced diabetes (5 mL/kg body weight), where drug showed significant antihyperglycemic efficacy [7]. So, Subetta contains RAD of Abs to β -InsR and RAD of Abs to eNOS.…”
Section: Methodsmentioning
confidence: 99%
“…In experimental model of streptozotocin-induced diabetes Subetta showed pronounced antihyperglycemic activity, which is comparable to that of the reference drug Rosiglitazone: Subetta decreases high plasma levels of glucose, urine levels of ketone bodies and improves glucose uptake in peripheral tissues [7]. Toxicological studies proved a high safety of the drug.…”
Section: Introductionmentioning
confidence: 93%
“…Кроме того, препарат увеличивает чувствительность тка-ней к действию инсулина, стимулируя инсулин-индуцированный захват глюкозы мышечными клетками человека in vitro [46]. На моделях СД1 и СД2 препарат продемонстрировал антигипергли-кемическую активность: значимо снижал повы-шенное содержание глюкозы в плазме, не вызывая гипогликемии, а также восстанавливал нарушен-ную толерантность тканей к глюкозе [47,48]. Пер-вые клинические данные у пациентов с СД2, полу-чающих либо метформин, либо базальный инсулин в сочетании с метформином, показали, что вклю-чение субетты в терапию приводит к значимому снижению уровня глюкозы в плазме натощак и гликированного гемоглобина, оказывает нормали-зующее действие на суточный профиль гликемии, а также существенно снижает уровень общего хо-лестерина в плазме [49].…”
Section: активация и потенцирование инсулиновой сигна-лизации улучшеunclassified